RETRACTED: Modeling the processes of vibroacoustic dynamics of the acoustic subsystem “drill-blanket” - Khinikadze Ildar; Chukarin Alexander; Finochenko Tatiana (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 549, 00001 (2024), https://doi.org/10.1051/e3sconf/202454900001